The State of University Policy for Progress in Europe - Cécile Hoareau; Jo Ritzen; Gabriele Marconi (Institute for the Study of Labor (IZA), 2012)
Higher education contributes to economic innovation. This study measures and compares the extent to which national governments policies foster this contribution across Europe. The study stresses the relevance of policies which are empowering for higher education institutions, or in other words provide them with appropriate resources and regulatory environments. The assessment relies on quantitative scores, based on the contribution of policies regarding funding and autonomy to higher education performance in education, research and economic innovation, using non-arbitrary weights and eighteen policy indicators across 32 European countries. A large number of countries belong to a middle group in our overall assessment, indicating a relative cohesion in Europe. Yet, substantial variations exist in terms of higher education policy in Europe, each European country having room for policy improvement.
Keywords: I23; I28; J24; L38; O31; O38; O43; O52; 330; higher education; research; innovation; Europe; public policy; institutions; Hochschulpolitik; Bildungspolitik; Universitäre Forschung; Innovation; Europa